Юридические лица как жертвы преступлений: постановка проблемы - K. A. Ilyasova (Russian Journal of Economics and Law)
Objective: to study victimological aspects of the crimes committed against legal persons; to formulate scientific problems associated with victimological characteristic of legal entities and to develop ways of solving them; to study the experience of foreign countries, exploring victimological aspects of legal entities; to define corporate victimology factors of legal persons. Methods: the dialectical method of cognition. Results: basing on the evaluation of opinions of various scholars and the analysis of the Russian and foreign legislation, the approach was proposed to study the victimological characteristics of legal persons. Scientific novelty: certain institutions were identified as individual objects of victimological impact, which differ from personal characteristics of the individual victims, who are not covered by previous victimological research. Practical value: conclusions and suggestions, as well as the results of the study, can be used in legislative activity on legislation improvement aimed at combating crimes committed against legal persons, the improvement of the prevention system of crimes committed against legal persons, in particular, the organization of victimological prevention of these crimes.